2022
DOI: 10.1055/s-0042-1758734
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Lungs—Emerging Challenges in Adult Cystic Fibrosis Care

Abstract: Cystic fibrosis (CF) is a multisystem disease. This article provides an up-to-date review of many of the nonrespiratory complications of CF, including mental health issues, nutritional and gastrointestinal problems, fertility issues, diabetes mellitus, bone health and musculoskeletal problems, liver disease, renal problems, and risk of malignancy. It highlights the recent impact of new therapies, including CF transmembrane conductance regulator modulators, on the nonrespiratory complications of CF and provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…In addition, a previous study on people with CF at the CF centre in Gothenburg showed no patient group-specific anatomical change or thoracic configuration with ageing [ 30 ]. Similar to the findings on thoracic mobility, these findings represent aspects of musculoskeletal health that need monitoring due to the demographic shift that is currently being seen in this patient group [ 11 , 31 ]. Regarding lung function, the results from this study were consistent with already well-established knowledge regarding the progressive nature of the disease on lung structure and function and will therefore not be discussed further at this time.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, a previous study on people with CF at the CF centre in Gothenburg showed no patient group-specific anatomical change or thoracic configuration with ageing [ 30 ]. Similar to the findings on thoracic mobility, these findings represent aspects of musculoskeletal health that need monitoring due to the demographic shift that is currently being seen in this patient group [ 11 , 31 ]. Regarding lung function, the results from this study were consistent with already well-established knowledge regarding the progressive nature of the disease on lung structure and function and will therefore not be discussed further at this time.…”
Section: Discussionsupporting
confidence: 60%
“…As the average age of people with CF increases, so will the challenges of managing typical age-related musculoskeletal conditions, and it will be necessary to explore how these can best be managed. As also highlighted in previous research [ 12 , 31 , 32 ], this will probably require new and multidisciplinary approaches.…”
Section: Discussionmentioning
confidence: 85%
“…They are at risk for chronic kidney disease from microvascular complications and repeat exposure to nephrotoxic antibiotics. CFLD is the third largest cause of mortality in pwCF and studies show the incidence increase into adulthood [50 ▪▪ ]. There is also an increased risk for osteoporosis, hearing loss, and malignancy [51].…”
Section: Aging With Cystic Fibrosis – Uncharted Territorymentioning
confidence: 99%